A PRELIMINARY NOVEL STUDY ON THE GRAVITY EFFECTS OF CURING OR DRYING ANGLE ON LAMINATED COMPOSITE STRUCTURE - YAAKOB, MOHD YUHAZRI (2012)
The composites materials are getting more attention nowadays for its superior properties such as light weight, high structural rigidity and high resistance to environment degradation. Its wide applications for instance in construction, automobiles and aircraft are encouraged by its easy fabrication method. Thus, its demand is very great. However, the current technique for curing or drying the composites occupies ample area. It is because the composites are laid flat horizontally for about 24 hours if room temperature curing is preferred. Therefore, the composites take up much space for long hours to reach complete drying. Consequently, the optimum productivity is not achieved. In order to meet the production delivery, much cost may be involved for getting required space for curing the composites. To handle this challenge, a study on the gravity effects of curing or drying angle on laminated composite structure via vacuum bagging technique is carried out. The study aims to identify the possibility of curing the composites at a certain angle position to reduce the space required in accordance with Lean concept to minimize wastage in terms of time, space and cost. The objectives is to investigate the mechanical properties through flexural, tensile and hardness testing for the laminated composites cured between 00 - 900. Besides, the physical properties such as density, water absorption and swelling are studied since their properties may affect the product applications during service. The composite structures are divided into top, middle and bottom regions to observe whether its properties vary due to the gravity effect. The research targets to have the best curing effect between 00 - 900 and may not or negligible effects on the different region of the composite structures. In short, the research is intended to facilitate composites manufacturing factories especially Small and Medium Industry (SMI), automobiles and ship industries.